2020
DOI: 10.1002/mame.202000129
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic, Pore‐Tunable Polyimide/Polyvinylidene Fluoride Composite Aerogels for Effective Airborne Particle Filtration

Abstract: Polyimide (PI) aerogels have great potential as filter materials, owing to their unique porous structure and excellent thermodynamic properties. In this work, polyvinylidene fluoride (PVDF) is introduced into the 3D network structure of crosslinked PI by phase separation to prepare PI/PVDF hybrid aerogels. By adding different amounts of PVDF, effective control of the aerogel porous structure is achieved, as a result, the air permeability of the hybrid aerogel is significantly improved while still achieving a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…However, the P12 and P9 samples have a higher specific surface area, 145 and 168 m 2 g −1 , respectively, in comparison with the prepared with ethanol of 113 and 136 m 2 g −1 for P12E0.2 and P9E0.2, respectively; these variations could be related to changes in the particles’ morphologies. In general, the obtained specific surface areas in this work are comparable with the ones reported in the literature of around 100 m 2 g −1 [ 16 , 32 , 52 ]; nevertheless, some authors reported PVDF–graphene composite aerogels with specific surface areas as high as 200 m 2 g −1 , which is attributed to the intrinsic graphene surface area [ 33 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, the P12 and P9 samples have a higher specific surface area, 145 and 168 m 2 g −1 , respectively, in comparison with the prepared with ethanol of 113 and 136 m 2 g −1 for P12E0.2 and P9E0.2, respectively; these variations could be related to changes in the particles’ morphologies. In general, the obtained specific surface areas in this work are comparable with the ones reported in the literature of around 100 m 2 g −1 [ 16 , 32 , 52 ]; nevertheless, some authors reported PVDF–graphene composite aerogels with specific surface areas as high as 200 m 2 g −1 , which is attributed to the intrinsic graphene surface area [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…Several synthetic approaches are focused on obtaining PVDF materials with a high content of the polar phases, including melting, mechanical stretching [ 12 , 13 , 14 ], annealing [ 15 , 16 ], blending [ 17 , 18 ], or addition of fillers [ 19 , 20 , 21 ], among others. However, such processing and fabrication techniques are impractical for certain materials, or they are not compatible with the final device design, thus stressing the importance of the exploration of alternative routes such as a precise crystal growth control [ 16 , 17 , 22 , 23 , 24 ]. Currently, different methods are being investigated to prepare PVDF materials such as fibers, films, or membranes exhibiting good piezoelectric properties; nonetheless, their performance is still far from alternative dense inorganic piezoelectric counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme hydrophobic nature of fluorocarbon resin can reduce the hydrophilicity of the PI aerogels. 117 Hybrid PI aerogels have also been investigated mainly by including polyvinylidene fluoride (PVDF) into the network, and WCAs of up to 1471 118 and 1521 119 have been reported. Apart from the aforementioned techniques, designing novel chemical backbones can also lead to hydrophobicity in PI aerogels.…”
Section: Wettability Propertiesmentioning
confidence: 99%
“…The inherent characteristics of the fillers expand and improve the performance of the polymer foams, thus making their composite foams more extensive in application. These composite foams are widely used in electromagnetic shielding, 3 environmental protection, 4 sensors, 5 energy collection, 6 and so on. Most of these composites are mainly filled with 2D nanostructures.…”
Section: ■ Introductionmentioning
confidence: 99%